Analysis of damage in relation to different classifications of pre-collapse osteonecrosis of the femoral head. Issue 2 (February 2018) - Zhang, Ying; Tian, Kewei; Ma, Xianghao; Zhang, Leilei; Sun, Ruibo; Wang, Huichao; Liu, Youwen; Zhou, Guangquan
Objective: This study aimed to investigate the damage pattern of the stress transfer path (STP) for the Japanese Investigation Committee (JIC) classification of pre-collapse osteonecrosis of the femoral head. We aimed to provide a specific biomechanical basis for treatment decisions of each subtype. Methods: Five computational models were used in the experiment. Different necrotic classifications were simulated based on the JIC classification system. Damage patterns of the STP were used for qualitative assessment and average stresses were used for quantitative analysis. Results: The STP of type A showed a strong similarity to the healthy level, which was consistent with the bone density distribution in X-rays and previous simulations results. The damaged area of principal stress of type B was approximately 25% of the healthy level. The STPs of types C1 and C2 were broken and the damaged areas of principal stress were more than 50% of the healthy level. The efficiency of stress transfer was reduced. Conclusions: These results indicate that the damage patterns and stress transfer efficiency of the femoral head are associated with necrotic classifications.